Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan PT. Reffel Kreasi Berkat Tahun 2025 - Mike Syafarah; Muhammad As'ad (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.Given the rapid growth of the creative and digital industries, companies must continuously boostproductivity to stay competitive. PT Reffel Kreasi Berkat, a company operating in the salon services sector,also faces productivity challenges, specifically fluctuations in employee morale. Signs of this issue includedecreased initiative, delayed task completion, and reduced active participation in team activities. If thistrend continues, it will negatively impact the company's business operations. This research aims todetermine the effect of compensation and work environment on employee morale. The samplingtechnique used was saturated sampling, with a total sample of 60 persons. The analysis was performedusing multiple linear regression. Data was obtained through questionnaires distributed to employees at PTReffel Kreasi Berkat. The research findings indicate that: partially, Compensation does not have astatistically significant and negative effect on employee morale, with its contribution estimated at 38.4%. Conversely, Work Environment significantly and positively affects employee morale at PT Reffel Kreasi Berkat, with its contribution being 66,2%. Collectively (simultaneously), both Compensation and WorkEnvironment significantly influence Employee Morale, accounting for a combined contribution of 66.4%. Keywords: Compensastion, Work Enviroment, Employee Morale